2022
DOI: 10.3390/ijms232112732
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptides Mediate Apoptosis by Changing Mitochondrial Membrane Permeability

Abstract: Changes in mitochondrial membrane permeability are closely associated with mitochondria-mediated apoptosis. Antimicrobial peptides (AMPs), which have been found to enter cells to exert physiological effects, cause damage to the mitochondria. This paper reviews the molecular mechanisms of AMP-mediated apoptosis by changing the permeability of the mitochondrial membrane through three pathways: the outer mitochondrial membrane (OMM), inner mitochondrial membrane (IMM), and mitochondrial permeability transition po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 75 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…A past study showed that the polysaccharides in C. pilosula may induce tumor cell apoptosis by activating the mitochondrial apoptotic pathway. The mechanism of apoptosis may be related to increasing the mitochondrial membrane permeability [ 25 ], promoting the release of cytochrome C, and activating downstream caspase 3 through a cascade reaction.…”
Section: Resultsmentioning
confidence: 99%
“…A past study showed that the polysaccharides in C. pilosula may induce tumor cell apoptosis by activating the mitochondrial apoptotic pathway. The mechanism of apoptosis may be related to increasing the mitochondrial membrane permeability [ 25 ], promoting the release of cytochrome C, and activating downstream caspase 3 through a cascade reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Depolarization of the mitochondrial membrane potential (MMP) directly affects the normal function of mitochondria and is an important indicator for observing early apoptosis . When the MMP collapses, it leads to mitochondrial membrane permeabilization and Cyt c leakage into the cytoplasm, which activates apoptosis. , Combined with the reduced ATP12 protein expression found in the proteome and the observed swelling of mitochondria, disruption of the inner membrane structure, and leakage of the contents, this suggests that the destruction of mitochondria by P852 is drastic. The results showed that P852 induced mitochondrial damage, content leakage, and MMP collapse in F.…”
Section: Resultsmentioning
confidence: 99%
“…The cGAS-STING pathway regulates several pathological processes brought on by the immunological response to the ectopic localization of self-DNA, including cytosolic mitochondrial DNA, in addition to protecting cells against a variety of DNA containing pathogens. Besides its well established antimicrobial properties, melittin creates pores in the cell membrane and the mitochondrial membrane, and may lead to exposure of mitochondrial DNA in the cytoplasm of cancer cells (Díaz-Achirica et al, 1994;Wang et al, 2022). It also causes morphological changes in the cell membrane and DNA damage in leukocytes even at noncytotoxic doses (Guha et al, 2021).…”
Section: Possible Anticancer Mechanisms Of Bioactive Compounds Isolat...mentioning
confidence: 99%